Effect of IL-33 on pyroptosis of macrophages in mice with sepsis via NF-κB/p38 MAPK signaling pathway - Ke,Jingnuan (2021)
ABSTRACT Purpose To demonstrate the effect of IL-33 on the macrophage pyroptosis in mice with sepsis through the NF-kB/p38 MAPK signal pathway. Methods In total, 24 C57BL/6 mice were divided into the sham operation group (sham) and the cecal ligation and puncture group (CLP). After CLP, 24 IL-33-/- mice were divided into the IL-33-/- group and the IL-33-/- intervention group. The latter group was intraperitoneally injected with IL-33. Mouse mortality was observed after CLP. Macrophage apoptosis in peritoneal lavage fluid was detected by flow cytometry. Serum inflammatory factor level was detected by ELISA. Apoptotic protein expression and NF-κB/p38 MAKP signaling pathway protein expression were detected by qRT-PCR and Western blot. Results Knocking out IL-33 significantly reduced the mortality of CLP mice, as well as the mRNA expression of IL-33 and the levels of serum inflammatory factors, including IL-33, IL-1β, and IL-18. It also reduced the rate of macrophage apoptosis and the expression of the apoptotic protein caspase-1 p10; increased the expression of IκBα; and reduced the protein expression of NF-κB and p38 MAPK. These effects were reversed after exogenous injection of IL-33. Conclusions IL-33 can increase the level of macrophage pyroptosis in mice with sepsis (by activating the NF-kB/p38MAPK signal pathway) and the mortality of these mice.